Perbandingan Kualitas Minyak Atsiri Gagang Cengkeh Basah dan Kering (Eugenia aromaticum) dengan Metode Destilasi Uap Air - Nahrowi, Fauzan; Handayani, Catur Budi; Asmoro, Novian Wely (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2023)
The purpose of this study was to determine the quality of essential oils from wet clove handles and dry clove handles. The experimental design in this study was a completely randomized design (CRD) with 2 treatments, namely wet handle and dry handle with 3 replications in each treatment. The results of this study showed that there was a significantly different interaction (p<0.05) including, water content, yield, refractive index, eugenol content between wet and dry clove handle treatments and the interaction did not have a significantly different interaction (p>0.05) including weight types between wet and dry clove handle treatment with moisture content value of wet clove handle 63.67% and dry clove handle moisture content 12.96%, essential oil yield value of wet clove handle 0.16% and essential oil yield of dry clove handle 0, 39%, the value of the specific gravity of wet clove handle essential oil 1044.22 g/ml and the dry clove handle essential oil value of 1042.22 g/ml, the value of the refractive index of the wet clove handle essential oil 1.471 and the refractive index of the dry clove handle essential oil 1.473, the value of eugenol content of wet clove handle essential oil 95.56% and dry clove handle essential oil 94.73%. The best essential oil treatment was found in the wet clove handle treatment with a value of 95.56% eugenol content.Keywords: clove handle, chemical characteristics, essential oil